Profile of the Bais Bay Basin - Calumpong, Hilconida P.; Luchavez, Julieta A. (Silliman Journal, 2023)
Bais Bay is located on the eastern side of Negros Island (123° 9" E long. 9° 34’ N lat.) facing Tafion Strait in Central Philippines, 45 km north of Dumaguete City. It occupies an area of about 54 km? (5,430 ha), naturally divided into North Bais Bay and South Bais Bay by Daco or Dewey Island. Near the center of North Bais Bay stands the smaller Olympia Island or Polundyot (also called Diutay Island) which unlike Daco island has no road connection to Bais City. Both islands are coral rocks with a very thin layer of about 1-2 inches of topsoil (Cadelifia, 1983) and are populated.